The seven step approach to the application of Sports Science in English professional rugby league: Practical considerations in strength and conditioning - Sanctuary, C. E.; Meir, R.; Sadler, I. (International Journal of Sports Science and Coaching, 2012)
This article examines the training and competition loads performed with a full-time professional rugby league team during a Super League season (pre- and in-season). While a logical and evidence-based approach was taken, involving initial planning, delivery, monitoring and evaluation, the idiosyncratic aspects of such a professional environment required a high degree of tacit knowledge and adaptability. The current article will therefore describe the context, outline the broad process and approach, provide some detailed case examples of support work undertaken with associated data, and identify the methods for evaluation. The use of four case studies (i.e., injury audit; hydration in a training week; alternative training strategy; and monitoring) helped review and inform strength and conditioning practice within a professional rugby league club environment.